Talent hunt for next generation of Olympians goes online (2008)
eTID: unearthing future Olympians for Australia. The search is on to find Australia's next gold medal hopes, with an eye on the London 2012 Olympics and beyond. With competition from other nations increasing, Australia is embarking on a world first initiative that will uncover talented hopefuls from every corner of the nation. In the lead up to the Beijing Games, the Australian Sports Commission's (ASC) has launch an online electronic talent identification program (better known as eTID). The system was the brainchild of the ASC's successful National Talent Identification and Development program which seeks to identify and develop Australia's future sporting talent. eTID is a simple to use, free, online program that allows anyone (aged 12-29) to assess their sporting potential. It provides opportunities for aspiring or current athletes and even former elite athletes looking to start a new sport. The athletes' information is processed and if identified as 'above average' by eTID they are then encouraged to visit a Talent Assessment Centre (TAC) to have their results verified. The TAC system is a collaboration between the ASC and over 20 universities throughout Australia. Such a collaboration to seek out talent has never occurred before and through this method the capability to hunt for talented athletes has been greatly expanded. Once a TAC identifies that the athlete has real talent they can then enter the elite sporting system, where they could be supported with coaching, equipment and travel. The link to the eTID website is: http://www.ausport.gov.au/media/releases/talent_hunt_for_london_2012_goes_online/etid_-_online_electronic_talent_identification_program